2018
DOI: 10.3390/educsci8040166
|View full text |Cite
|
Sign up to set email alerts
|

What Biological Visualizations Do Science Center Visitors Prefer in an Interactive Touch Table?

Abstract: Hands-on digital interactivity in science centers provides new communicative opportunities. The Microcosmos multi-touch table allows visitors to interact with 64 image “cards” of (sub)microscopic biological structures and processes embedded across seven theme categories. This study presents the integration of biological content, interactive features and logging capabilities into the table, and analyses visitors’ usage and preferences. Data logging recorded 2,070,350 events including activated category, selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A value of 1 indicated that an image was always selected, irrespective of what other image it was combined with, while a value of 0 would show that the image was never selected. To compare how the scores and the resulting ranking of images related to each other and to findings from usage statistics from the Microcosmos exhibit, Spearman's rank correlation was calculated between the scores for image preference, perceived realism, desire to explore, and relative ranking of the individual images based on data from a previous study (Höst et al, 2018). Screenshot of the data collection interface, with one example of a pair of images taken from the Microcosmos exhibit (Höst et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A value of 1 indicated that an image was always selected, irrespective of what other image it was combined with, while a value of 0 would show that the image was never selected. To compare how the scores and the resulting ranking of images related to each other and to findings from usage statistics from the Microcosmos exhibit, Spearman's rank correlation was calculated between the scores for image preference, perceived realism, desire to explore, and relative ranking of the individual images based on data from a previous study (Höst et al, 2018). Screenshot of the data collection interface, with one example of a pair of images taken from the Microcosmos exhibit (Höst et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To compare how the scores and the resulting ranking of images related to each other and to findings from usage statistics from the Microcosmos exhibit, Spearman's rank correlation was calculated between the scores for image preference, perceived realism, desire to explore, and relative ranking of the individual images based on data from a previous study (Höst et al, 2018). Screenshot of the data collection interface, with one example of a pair of images taken from the Microcosmos exhibit (Höst et al, 2018). In this example, participants are asked to indicate which image they would like to explore further, as an indication of their interaction intention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visitors can interact directly with the visualizations, they can perform single and multi touch gestures, e.g, rotate the volume or cut through it, but they cannot select objects very precisely. Similar setups are used to explore a virtual human mummy [YRA*16] and biological structures that would not be visible to the naked eye [HSFT18]. However, besides pre-defined transfer functions, textual descriptions, and videos no further guidance through the complex data is provided.…”
Section: Selected Examples Of Narrative Scientific Visualizationmentioning
confidence: 99%